PENGARUH MOTIVASI, DISIPLIN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI HOTEL MORRISSEY JAKARTA - Agus Riyanto; Nur Nadya Jasmine (LPPM Universitas Asa Indonesia, 2018)
Purpose- This study aims to determine the influence of motivation, discipline and environment’s work simultaneously and partially on employee performance. The population in this study were employees of Hotel Morrissey Jakarta. Design/methology/approach- The sample used in this research is employees of Hotel Morrissey Jakarta as many as 100 people. The sampling technique used is accidental sampling. Data collection techniques using field research. The data were analyzed by validity test, reliability test, classic assumption test (normality test, multicollinearity test, heteroskedasticity test, linearity test) and multiple linear regression analysis while hypothesis testing included F test, T test and correlation and determination coefficient test (R2). Findings- The results of the analysis can be known the influence of motivation, discipline and work environment affect the employees performance either partially or simultaneously